2003
DOI: 10.1038/sj.jea.7500259
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride concentrations in three types of commercially packed tea drinks in Taiwan

Abstract: Tea is a popular drink around the world. It is also one of the major sources of fluoride intake. The objectives of this study were to assess fluoride concentrations in popular non -, semi -, and full -fermented tea drinks sold on the Taiwan market. Concentration differences among three types of commercially available tea drinks ( tea leaf, tea bag, and packaged tea beverage ) were explored. Several influential factors in intake concentrations were evaluated. The acute threshold intake ( ATI ) and allowable dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
3
24
0
1
Order By: Relevance
“…The variation of the first four tea drinks was close to the variation of triplicate samples, while the large variation of pureh was mainly due to the low fluoride concentrations. In addition, previous study showed that fluoride infused from black tea did have higher variation compared to other tea drinks (%CV of black tea was up to 20%, Lung et al, 2003); this may account for high variation of black tea in this experiment. Thus, our results suggest that the use of glass tea makers or porcelain teapots would not affect fluoride levels in tea infusions for these tea leaves.…”
Section: Influence Of Containersmentioning
confidence: 91%
See 1 more Smart Citation
“…The variation of the first four tea drinks was close to the variation of triplicate samples, while the large variation of pureh was mainly due to the low fluoride concentrations. In addition, previous study showed that fluoride infused from black tea did have higher variation compared to other tea drinks (%CV of black tea was up to 20%, Lung et al, 2003); this may account for high variation of black tea in this experiment. Thus, our results suggest that the use of glass tea makers or porcelain teapots would not affect fluoride levels in tea infusions for these tea leaves.…”
Section: Influence Of Containersmentioning
confidence: 91%
“…However, porcelain and pottery teapots are used in traditional tea making. It has been reported that there was no difference in fluoride concentrations by using glass or pottery tea makers (Lung et al, 2003). Thus, we only assessed fluoride levels in tea infusions in glass and porcelain containers.…”
Section: Assessment Of Potential Factorsmentioning
confidence: 99%
“…Hudaykuliev et al [21] reported a range of F content for Turkish teas as 88-289 mg/kg which corresponds to 0.8-2.6 mg/l infusion concentrations with the assumption of water-soluble fraction is 90%. Higher levels were reported from other parts of the world as 0.45-6.5 mg/l [7,10,11,18]. The highest concentrations (4.8-7.3 mg/l) occurred in brick tea infusions after 6 h of infusion [19].…”
Section: Fluoridementioning
confidence: 93%
“…The estimated mean daily tea intake in this study (0.49 l/day) is about half the assumed consumption by Kalayci and Somer [17], but it is approximately three times higher than Fernandez et al [30] assumption. Nevertheless, it is much less than the consumption rates (0.8-0.9 l/day) in Southern Asia [11,18].…”
Section: Questionnaire Datamentioning
confidence: 98%
See 1 more Smart Citation